The Roles and Mechanisms of lncRNAs in Liver Fibrosis - Wang, Zhifa; Yang, Xiaoke; Gui, Siyu; Yang, Fan; Cao, Zhuo; Cheng, Rong; Xia, Xiaowei; Li, Chuanying (Frontiers in Pharmacology, 2021)
Long non-coding RNAs (lncRNAs) can potentially regulate all aspects of cellular activity including differentiation and development, metabolism, proliferation, apoptosis, and activation, and benefited from advances in transcriptomic and genomic research techniques and database management technologies, its functions and mechanisms in physiological and pathological states have been widely reported. Liver fibrosis is typically characterized by a reversible wound healing response, often accompanied by an excessive accumulation of extracellular matrix. In recent years, a range of lncRNAs have been investigated and found to be involved in several cellular-level regulatory processes as competing endogenous RNAs (ceRNAs) that play an important role in the development of liver fibrosis. A variety of lncRNAs have also been shown to contribute to the altered cell cycle, proliferation profile associated with the accelerated development of liver fibrosis. This review aims to discuss the functions and mechanisms of lncRNAs in the development and regression of liver fibrosis, to explore the major lncRNAs involved in the signaling pathways regulating liver fibrosis, to elucidate the mechanisms mediated by lncRNA dysregulation and to provide new diagnostic and therapeutic strategies for liver fibrosis.